2021
DOI: 10.3390/electronics10202531
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Tire Mileage and Wear Using Measurement Data

Abstract: Tire mileage and wear provide important information for vehicle applications. There are more and more studies discussing intelligent tires, but few focus on the role of tire mileage and wear. The conventional tire pressure monitoring system (TPMS) is one of the intelligent tire applications, but there has been no significant advancement in recent years in this regard. In order to increase the additional functions of intelligent tire applications, we propose a method that estimates the mileage and wear informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It is found in the literature [8,11] that most researchers have discussed their research outcomes using various models where the experimental results support the case model-based analyses. Apart from various models, a regression analysis is one of the most powerful statistical methods for examining the relationship between two or more variables of interest.…”
Section: Regression Analysismentioning
confidence: 80%
See 2 more Smart Citations
“…It is found in the literature [8,11] that most researchers have discussed their research outcomes using various models where the experimental results support the case model-based analyses. Apart from various models, a regression analysis is one of the most powerful statistical methods for examining the relationship between two or more variables of interest.…”
Section: Regression Analysismentioning
confidence: 80%
“…Te researchers in [6,7] have also shown that tire safety and road vehicle stability, as well as driver and passenger satisfaction, are related to tire quality, tire material, appropriate tire size, and inadequate tire characteristics. According to previous research [3,[8][9][10][11][12], most researchers measured tire wear using various approaches, such as the fnite element method (FEM) and the analytical method, with most case modelbased analyses supporting the experimentally measured data. Te quantity of tire wear is predicted numerically for use in tire design [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation